2020
DOI: 10.1093/mnras/staa2027
|View full text |Cite
|
Sign up to set email alerts
|

From rest-frame luminosity functions to observer-frame colour distributions: tackling the next challenge in cosmological simulations

Abstract: Abstract Galaxy spectral energy distributions (SEDs) remain among the most challenging yet informative quantities to reproduce in simulations due to the large and complex mixture of physical processes that shape the radiation output of a galaxy. With the increasing number of surveys utilising broadband colours as part of their target selection criteria, the production of realistic SEDs in simulations is necessary for assisting in survey design and interpretation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 93 publications
1
13
0
Order By: Relevance
“…We are now able to simulate the physics of galaxy formation and, to some extent, link galaxy properties to the host halo properties. For example, the UNIVERSEMACHINE (Behroozi et al 2019) that reasonably parametrizes the galaxy growth-halo assembly correlation and the SHARK (Lagos et al 2018) that agrees fairly well with observations (Bravo et al 2020). But there is still a need for improvement in understanding the process of galaxy formation (see Naab & Ostriker 2017, for a review).…”
Section: Introductionmentioning
confidence: 71%
“…We are now able to simulate the physics of galaxy formation and, to some extent, link galaxy properties to the host halo properties. For example, the UNIVERSEMACHINE (Behroozi et al 2019) that reasonably parametrizes the galaxy growth-halo assembly correlation and the SHARK (Lagos et al 2018) that agrees fairly well with observations (Bravo et al 2020). But there is still a need for improvement in understanding the process of galaxy formation (see Naab & Ostriker 2017, for a review).…”
Section: Introductionmentioning
confidence: 71%
“…1), we intentionally crosscontaminate the two populations in TNG100. Bravo et al (2020) have shown that assuming a fractional contamination between centrals and satellites closely mimics the procedure of running a group catalogue in a simulated galaxy lightcone and assessing contamination there. In a similar vein, we use weights when calculating statistical quantities (means, medians, and other percentiles) for TNG100 satellites or centrals, which are assigned to ensure we get back a desired effective purity.…”
Section: Cross-contamination Of Centrals and Satellitesmentioning
confidence: 92%
“…In this work, we use the semi-analytic model (SAM) (L18), which has been shown to reproduce a wide variety of observations (Amarantidis et al 2019;Davies et al 2019a;Lagos et al 2019Lagos et al , 2020Chauhan et al 2019Chauhan et al , 2020Chauhan et al , 2021Bravo et al 2020). Most critical for this work are the excellent predictions of observed number counts, luminosity functions (Lagos et al 2019(Lagos et al , 2020 and low-redshift colour distributions (Bravo et al 2020). Briefly, a SAM generates and evolve galaxies using dark matter (DM) only N-body simulations, by following a set of equations that described the relevant physical processes to galaxy evolution.…”
Section: Simulated Catalogues ( )mentioning
confidence: 99%
“…We leave how to connect the central black hole properties in to the AGN SEDs in P S for future work. Following Lagos et al (2019); Bravo et al (2020), we use their parameterisation model for dust 5 , which uses the best-fit dust fraction-to-gas metallicity ratio from Rémy-Ruyer et al (2014) to calculate Σ dust , and then apply the Charlot & Fall (2000) parameters Σ dust -dependency found in Trayford et al (2020). For a more detailed description, we refer the reader to Sections 2.1 and 3.1 of Lagos et al (2019).…”
Section: Simulated Catalogues ( )mentioning
confidence: 99%